The value of ultrasonography of skeletal muscles in chronic obstructive pulmonary disease patients - Hadeer Ahmed Elshahaat; Ahmad Abbas; Rabab Mahmoud Elfwakhry; Mohamed Taher Anwar (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background The evaluation of skeletal muscles and diaphragm is not frequently carried out in patients with chronic obstructive pulmonary disease (COPD), despite the fact that muscle dysfunction is a significant contributor to morbidity in those patients. Aim Our study aimed to assess the usefulness of skeletal muscles’ (both respiratory, and non-respiratory) ultrasonography as a prognostic tool in patients with COPD in comparison with clinicometric, functional data Results This study was carried out at the chest department (intensive care unit, inpatient, and outpatient clinic) and involved 2 groups of adult patients (stable COPD, and acute exacerbation of COPD (AECOPD)), each group included 120 patients. The severity of COPD disease, COPD assessment test (CAT) score, spirometry, and 6-min walking test (6MWT) were evaluated and compared in both groups and the severity of exacerbation in the AECOPD group. Thicknesses of the diaphragm (DT), intercostal muscles (ICMs), and pectoralis major muscle and cross-sectional area of rectus femoris (RFCSA) muscle were measured by ultrasound and compared between both patients’ groups and between severity categories. Our study reported that functional (6MWT), physiological (spirometry) parameters and studied muscles’ thicknesses were highly statistically significantly lower in the AECOPD group. Also, it showed statistically significant differences among severity categories in both groups regarding previous parameters, where the lowest values being among the very severe group. According to the severity of exacerbation, there were also highly statistically significant reductions in the thicknesses of every muscle measured. After applying multivariate regression analysis for significant predictors of AECOPD, a number of previous exacerbations, CAT score, FEV1, DT, left 2nd, right 2nd ICM and RFCSA, and pectoralis major thickness were still significant. Also, shear wave elastography (SWE) of the diaphragm and intercostal muscles was done to assess muscle stiffness. Elastic modulus of diaphragm and ICM were highly statistically significantly higher in the AECOPD group, with the more stiff muscles reported in the very severe COPD group. Conclusion Respiratory and non-respiratory muscles ultrasound, as an effort-independent and radiation-free tool, is a promising and repeatable biomarker for muscle evaluation and offers valuable bedside information in assessing COPD severity and predicting frequent exacerbations.